Incentivos e barreiras para a realização do teste de HIV entre homens que fazem sexo com homens - Melo, Eugênia Marques de Oliveira (2012)
This work aims to explore the contexts of vulnerability that interfere on the (non) realization of the HIV test among men who have sex with other men. In a more specific way, it aims to explore which individual, social and programmatic factors may be established as encouragement and hurdles for the realization of the HIV test, outlining the vulnerability framework of the Men Who Have Sex with Men (MSM). It also explores how the recommendations of the Ministry of Health for the realization of the HIV test are extended and experienced by the MSM. The adopted theoretical reference was constructionist and the vulnerability framework was the reasoning used as a basis for the whole research. The study brings a general panorama of the aids epidemics among the MSM on a national and international level, as well as the international recommendations policy that have influenced the Brazilian responses to HIV/aids, and the building of national public policies that refer to the HIV test. This research has an exploratory character, qualitative approach, and used the methodology of Rapid Assessment, which has anthropological presuppositions. Forty semi-structured interviews were done with MSM who were at least 18 years of age, with both positive and negative serology for HIV, and who had never done the test, living in the city of Fortaleza. The interviews were done in many places around the city, aiming to get a wider sample of information, being a constant for the research only a NGO and a Service of Specialized Attention of Reference to HIV/aids. The information was analyzed through the technique of content analysis that was category-based. The results show that the reasons for the realization of the HIV test among the MSM were: they perceived they were at risk, a demand from the partner, self-care and fear of the disease, blood donation, encouragement from the healthcare professionals, prevention workshops and LGBT events. On the other hand, the barriers to the test were: poverty, lack of general knowledge about HIV prevention and transmission, prejudice against the non-heterosexual sexualities, stigma in relation to the homoerotic practices and to aids itself, homophobia, discrimination referring to aids and low or no perception of the risk. The pragmatic barriers were: lack of knowledge about the places, the procedure and reliable time to do the test, discredit for the test recommendation from the Ministry of Health, discredit for the efficiency of the quick test, homophobia, lack of preparation to deal with questions of the homoerotic sexuality and emotional reasons deriving from the positive results among the healthcare professionals, lack of and inefficient governmental campaigns for the stimulation to look for the diagnosis and lack of identification with the HIV/aids policies created for MSM when in everyday life there is no such identification. The results also show that these reasons have a direct impact on the non-following of the recommendations of testing, making the MSM population from Fortaleza vulnerable to the epidemics. Based on the wide concept of health, public policies must be elaborated taking into consideration the concept of integrality in such a way that this population can be assisted in their rights, which will have a consequence in the reduction of the vulnerability to the HIV/aids.